Paleoseismic Evidence of an Mw 7 Pre‐Hispanic Earthquake in the Peruvian Forearc. Issue 6 (17th June 2021) - Benavente, Carlos; Wimpenny, Sam; Rosell, Lorena; Robert, Xavier; Palomino, Anderson; Audin, Laurence; Aguirre, Enoch; García, Briant
Abstract: We present the results of a paleoseismic survey of the Incapuquio Fault System, a prominent transpressional fault system cutting the forearc of South Perú. High‐resolution Digital Elevation Models, optical satellite imagery, radiocarbon dating, and paleoseismic trenching indicate that at least 2–3 m of net slip occurred on the Incapuquio Fault generating a complex, ∼100‐km long set of segmented fault scarps in the early 15th century (∼1400–1440 CE). We interpret the consistent along‐strike pattern of fault scarp heights, geometries and kinematics to reflect a surface rupture generated by a single M w 7.4–7.7 earthquake, suggesting that brittle failure of the forearc poses a significant, yet mostly overlooked, seismic hazard to the communities in coastal areas of Perú. The timing of this earthquake coincides with the collapse of the Chiribaya civilization in ∼1360–1400 CE, and we present evidence of damaged buildings along the fault trace that may be of Chiribayas age. Our surface faulting observations, when combined with observations of deformation in the forearc from geodesy and seismology, also demonstrate that the forearc in South Perú experiences a complex, time‐varying pattern of permanent strain, with evidence for trench‐parallel shortening, trench‐parallel extension, and trench‐perpendicular shortening all in close proximity but in different periods of the megathrust earthquake cycle. The kinematics of recent slip on the Incapuquio Fault are consistent with the sense of interseismic strain within the forearc measured by GPS, suggesting the fault is loaded toward failure between megathrust earthquakes. Key Points: We describe a ∼100‐km long, 2–4‐m high segmented fault scarp in the forearc of southern Peru along the Incapuquio Fault System We argue that the scarps were formed during an M w 7.4–7.8 earthquake that ruptured the Incapuquio Fault in the early 15th century The kinematics of the Incapuquio Fault suggest that it breaks following strain accumulation in the forearc during the interseismic period of the megathrust earthquake cycle